Equinus Correction During Multilevel Surgery in Adults With Cerebral Palsy. (July 2018) - Putz, Cornelia; Mertens, Eva Maria; Wolf, Sebastian I.; Geisbüsch, Andreas; Niklasch, Mirjam; Gantz, Simone; Döderlein, Leonhard; Dreher, Thomas; Klotz, Matthias C.
Background: Equinus foot deformity constitutes a common gait disorder in ambulatory adults with bilateral spastic cerebral palsy (BSCP). The outcome after intramuscular aponeurotic lengthening in the context of single-event multilevel surgery (SEMLS) in adulthood has not been investigated. Methods: We followed a group of 31 ambulatory adults with BSCP and equinus who underwent SEMLS including gastrocnemius-soleus intramuscular aponeurotic recession or Achilles tendon lengthening. All patients were analyzed preoperatively and at least 1 year (mean follow-up period: 1.6 years) postoperatively by clinical examination and 3-dimensional instrumented gait analysis including the Gait Profile Score (GPS). Results: Clinical examination showed no significant improvement of ankle dorsiflexion ( P = .5) and an unchanged plantarflexion ( P = .7) with knee extended but a significant postoperative reduction of spasticity in the calf muscle ( P = .0001) as measured by clinical examination following the modified Ashworth scale. Significant improvement of mean ankle dorsiflexion in stance and swing ( P = .0001) was found. The GPS decreased and improved significantly (15.9 ± 4.6 to 11.4 ± 3.1; P = .0001). Persistence of equinus and calcaneal gait indicating under- and overcorrection at follow-up was found in 1 patient (3%), respectively. Conclusion: Intramuscular gastrocnemius-soleus aponeurotic recession is part of multilevel surgery corrected equinus deformity in adults. The increase in muscle length led to significant improvement of kinetic and kinematic parameters during walking without a loss of muscle strength and push-off capacity. The risk of overcorrection after equinus correction in adults with BSCP was found to be relatively low. Level of Evidence: Level IV, retrospective case series.